2020
DOI: 10.3390/nu12113445
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Effects Related to Food Habits and Lifestyle Changes Derived from COVID-19 Home Confinement in the Spanish Population

Abstract: As a consequence of COVID-19, millions of households have suffered mobility restrictions and changes in their lifestyle over several months. The aim of this study is to evaluate the effects of COVID-19 home confinement on the food habits, lifestyle and emotional balance of the Spanish population. This cross-sectional study used data collected via an anonymous online questionnaire during the month before lockdown finished in Spain, with a total of 675 participants. 38.8% of the respondents experienced weight ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
202
6
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(249 citation statements)
references
References 59 publications
22
202
6
19
Order By: Relevance
“…In our study, the frequency of alcohol drinkers who increased and that of those who decreased alcohol intake with lockdown was very similar, around 15%. Compared to other surveys, the frequency of increased alcohol consumption was much lower in our population than in adults in Germany (34.7%) (51), Australia (20.0% (52) to 30.8% (53)) or the USA (29%) (54), and more similar to that reported in other Spanish (14,22), French (45,55), and Italian surveys (56). In fact, in these studies, declining alcohol consumption during quarantine was more common than increasing it.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, the frequency of alcohol drinkers who increased and that of those who decreased alcohol intake with lockdown was very similar, around 15%. Compared to other surveys, the frequency of increased alcohol consumption was much lower in our population than in adults in Germany (34.7%) (51), Australia (20.0% (52) to 30.8% (53)) or the USA (29%) (54), and more similar to that reported in other Spanish (14,22), French (45,55), and Italian surveys (56). In fact, in these studies, declining alcohol consumption during quarantine was more common than increasing it.…”
Section: Discussionsupporting
confidence: 74%
“…A few studies have investigated the health consequences of the lockdown during the first wave of the pandemic in the Spanish adult population. Using convenience sample surveys conducted between March and June 2020, in which participants reported their perceived changes in lifestyle and health-related factors since the start of the pandemic, these studies have shown a general worsening in psychological and mental health (8–10), as well as in sleep quality (1113), mild or no changes in tobacco and alcohol consumption (11,14), slight or no changes in weight (1416), conflicting results for diet quality (17,18), important reductions in physical activity and increases in sedentary time (11,1921). Interestingly, one survey found that the percentage of interviewees meeting the guidelines regarding screen time became lower between March 22 nd and April 5 th , while unhealthy alcohol consumption and insufficient physical activity decreased during this three-week period (22).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings regarding sleep quality are in line with those of others carried out in the context of the pandemic, indicating that confinement is associated with worse sleep quality 30,31 . It is likely that forced confinement results in increased levels of stress/anxiety, as well inability to maintain a physically active lifestyle, which in turn are associates with poorer sleep quality [31][32][33] .…”
Section: Sleep Quality Among Women and Mensupporting
confidence: 92%
“…Participants who stayed at home/worked from home were less likely to go shopping in person or order food online, which suggested that they may spend more time cooking at home. López-Moreno et al showed that 73.5% people reported better cooking at home in a Spanish population during COVID-19 home confinement [ 14 ]. Similarly, Ruiz-Roso et al found that families had more time to cook at home during the pandemic [ 15 ].…”
Section: Discussionmentioning
confidence: 99%